The The Influence Of Work Environment And Quality Of Work Life (Qwl) Through Occupational Health And Safety (Ohs) On The Performance Of Inpatient Nurses At Hospital X In Jember: The Influence Of Work Environment And Quality Of Work Life (Qwl) Through Occupational Health And Safety (Ohs) On The Performance Of Inpatient Nurses At Hospital X In Jember - Agustin, Tata Lia; Tobing, Diana Sulianti K; Sudarsih (Study Program of Management Faculty of Economics and Business University of Jember, 2025)
This study aims to analyze the influence of the work environment and quality of work life (QWL) on the performance of inpatient nurses through occupational health and safety (OHS) at Hospital X in Jember. Employing a quantitative approach with an explanatory research design, data were collected through questionnaires distributed to 60 inpatient nurses and analyzed using the Partial Least Squares (PLS) method. The results indicate that the work environment does not have a direct effect on nurse performance but significantly affects OHS. Conversely, QWL has a significant effect on both OHS and nurse performance. Additionally, OHS significantly influences nurse performance and mediates the relationship between the work environment, QWL, and nurse performance. These findings underscore the importance of strengthening OHS implementation and improving work life quality to enhance the optimal performance of healthcare personnel.